Quantum energy method for diagnostics and competitive success forecasts in elite sports - Sivakov, V. I.; Aitkulov, S. A.; Cherkasov, I. F. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to explore the benefits of the quantum energizing method for the initiatives to improve the colour indices of the athletes` energy systems in the education, training and competitive process in individual and team sports. The quantum energizing method may be applied to rate the athletes` functionality and working capacity and forecast their competitive performance in individual and team sports by the colour indices of the energy systems. The quantum energizing method gives the means to select the potentially most successful athletes for the upcoming competitions (including the team compositions of the strongest and most energetic players having higher potential working capacity rates than their peers with relatively weaker tested competitive energy capacity). The quantum energy method facilitates the colour indices of the athletes` energy systems being improved in a high-intensity training process; secures progress of a variety of physical qualities including strength, speed and coordination abilities; and effectively develops the following energy supply mechanisms: anaerobic-lactate, anaerobic-glycolytic, anaerobic-aerobic, and aerobic. It should be noted that individual colour indices of energy systems and energy centres are determined by the functionality levels ranked as the low, average and high.